Knowledge and Perception of Facial Candling for Allergic Rhinitis among University Staff and Students. (3rd August 2020) - Hamdan, Nurul Khaleeda Athiraah; Lean, Qi Ying; Neoh, Chin Fen; Abdullah, Amir Heberd; Lim, Siong Meng; Ramasamy, Kalavathy; Al-Worafi, Yaser Mohammed; Goh, Khang Wen; Goh, Hui Poh; Ming, Long Chiau; Lua, Pei Lin
Abstract : Introduction . Facial candling is a traditional method used for relieving symptoms of allergic rhinitis (AR). This study aims to investigate the knowledge and perception of facial candling in a sample of staff and students in a public university in Malaysia. Methods . An online questionnaire survey method was used. Based on sample size calculation, a total of 1, 508 UiTM staff and students from ten selected campuses of Universiti Teknologi MARA (UiTM) were invited to participate in this survey. An up-to-date e-mail list of staff in the selected campuses was used as the sampling frame for the study, whereas the students were recruited from the official university student Facebook portal. Results . A total of 788 respondents participated in this survey, 72.2% of them knew about facial candling, though only 35.4% had tried the treatment. Approximately one-fifth of respondents agreed that facial candling might treat AR. It was found that a higher number of users than nonusers agreed that facial candling was a traditional medicine (78.9% vs 55.0%); could be used on the face and ears (83.5% vs 45.4%); and could be self-administered at home (83.5 vs 45.4%). Interestingly, more than half of them were uncertain about its long-term effects and adverse reactions. Conclusion . This study confirms the facial candling use among patients with AR although the percentage is low. The patients and general public need to be better informed about the use of facial candling in AR and its associated risks.